2002
DOI: 10.1254/jjp.90.59
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Dextran Sulfate Sodium-Induced Colitis in Kininogen-Deficient Rats and Non-peptide B2 Receptor Antagonist-Treated Rats

Abstract: ABSTRACT-Various proinflammatory mediators are believed to be involved in the processes and symptoms of ulcerative colitis (UC). To determine whether endogenous kinin enhances the severity of UC, we induced experimental colitis (EC) in kininogen-deficient mutant rats and tested the effect of a nonpeptide B2 receptor antagonist. EC was induced in male kininogen-deficient Brown Norway-Katholiek rats (BN-Ka) and normal Brown Norway-Kitasato rats (BN-Ki) with 5% dextran sulfate sodium (DSS). SpragueDawley rats (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…From a similar point of view, it would be of interest to investigate whether protein misfolding, FXII, and the kallikrein-kinin system are involved in the (unknown) etiology of inflammatory diseases. An example would be inflammatory bowel disease, which is in part mediated by BK and can be experimentally induced by oral administration of DXS to mice (47). Additionally, 2 recent publications have reported that the presence of the contaminant oversulfated chondroitin sulfate in certain preparations of heparin is responsible for serious adverse clinical events that are specifically attributed to activation of FXII and PK (48,49).…”
Section: Figurementioning
confidence: 99%
“…From a similar point of view, it would be of interest to investigate whether protein misfolding, FXII, and the kallikrein-kinin system are involved in the (unknown) etiology of inflammatory diseases. An example would be inflammatory bowel disease, which is in part mediated by BK and can be experimentally induced by oral administration of DXS to mice (47). Additionally, 2 recent publications have reported that the presence of the contaminant oversulfated chondroitin sulfate in certain preparations of heparin is responsible for serious adverse clinical events that are specifically attributed to activation of FXII and PK (48,49).…”
Section: Figurementioning
confidence: 99%
“…FR173657 is an orally active, nonpeptide BK B2 receptor antagonist that selectively inhibits BK binding to B2 receptors in rodents and humans (16). The dose chosen for each drug was as determined in previous studies (11,15,17). In cases of benazepril and FR173657, the doses previously determined for rats were used in mice in this study after adjustment of each mouse weight because the general pharmacology of both drugs was mostly identical in rats and mice (18 -20).…”
Section: Csa Nephropathy Model In Micementioning
confidence: 99%
“…Recently, we have demonstrated that in a model of colitis induced by 2,4,6‐trinitrobenzene sulphonic acid (TNBS) there was a marked increase of BK‐elicited contraction in vitro , associated with an enhancement of specific B 2 receptor‐binding sites in the mouse colon ( Hara et al ., 2007 ). Moreover, treatment with selective B 2 receptor antagonists was able to ameliorate dextran sulphate sodium‐induced colitis in both mice and rats ( Arai et al ., 1999 ; Kamata et al ., 2002 ). Finally, an alteration in both the distribution and levels of B 1 receptors was observed in the intestinal tissue of patients with IBD, suggesting a role for this receptor in intestinal inflammation ( Stadnicki et al ., 2005 ).…”
Section: Introductionmentioning
confidence: 99%